INFLUENCE OF DOUBLE SOLUTION TREATMENT ON HARDNESS IN 17-4 PH STEEL - Sowa, R.; Roga, E.; Arabasz, S.; Dziedzic, A.; Dul, I.; Kowal, A.; Parlinska Wojtan, M. (Journal of Engineering & Processing Management, 2015)
The investigated material is a corrosion-resistant, Cu precipitation hardened steel 17-4PH, which undergoes a macroscopic contraction, as a result of applying the following heat treatment: double solution treatment at 1028°C for 1 h (condition A), ageing at 540°C for 4 h (condition H1025). The second solution treatment at 1028°C was found to eliminate the retained austenite, being the evidence of a completely finished martensitic transformation.Indeed, the only phase identified in all samples was fcc lath martensite exhibiting a parallel striped structure. Unfortunately, this additional heat-treatment operation leads likewise to significant and irregular grain growth, which consequently causes a drop in material hardness. Moreover, the second solution annealing, caused a shift in the XRD peaks to higher 2θ angles, resulting from a lattice parameter decrease by0,25%. The two subsequent heat-treatment procedures bring the lattice parameter back to its initial value. This seemingly reversible process of decrease and increase of the lattice parameter was observed for samples subjected to all the heat treatment operations, strongly suggesting the existence of a relation between the microstructural changes and the macroscopic contraction of the steel material. In addition to the martensitic phase, in the unaged samples, a δ- ferrite phase could be identified by TEM and electron diffraction, which is favorable for ductility and toughness of the material. In all samples, non-coherent fcc-NbC precipitates identified by electron diffraction and EDX mapping having sizes up to 70 nm were found.